Compliance to anti rabies vaccine and animal bite management practices in a rural area of Davangere, Karnataka, India - R., Anandaraj; S., Balu P. (International Journal Of Community Medicine And Public Health, 2017)
Background: In India 20,000 deaths and 17.4 million animal bite cases occur annually. Rabies is not a notifiable disease in India and most deaths occur in rural areas where surveillance is poor.Objectives of the study were (i) to study the compliance of animal bite victims to anti rabies vaccination (ARV) and (ii) to study the wound management practices of animal bite victims. Methods:A cross sectional study was conducted in April - May 2014 in areas catered by Anaji primary health centre (PHC), Davangere, Karnataka, India. Category 2 and 3 animal bite victims registered in the past 3 years at Anaji PHC were visited at their residence and data was collected using a semi structured questionnaire. Results: About 23.4% reported 24 hours post bite to the health facility. Correct wound management was observed only in 12.5% of victims while 33.3% sorted to indigenous practices and 27.1% did not receive any wound care. 82.6% completed the ARV schedule while 17.4% did not complete the schedule. Lack of time (50%) was the most common reason for non-compliance. Conclusions:Compliance to ARV was good yet declined after the third dose. Correct wound management practices were not done for majority of animal bite victims.